2009
DOI: 10.1186/1471-2458-9-5
|View full text |Cite
|
Sign up to set email alerts
|

Pastoralism and delay in diagnosis of TB in Ethiopia

Abstract: Background: Tuberculosis (TB) is a major public health problem in the Horn of Africa with Ethiopia being the most affected where TB cases increase at the rate of 2.6% each year. One of the main contributing factors for this rise is increasing transmission due to large number of untreated patients, serving as reservoirs of the infection within the communities. Reduction of the time between onset of TB symptoms to diagnosis is therefore a prerequisite to bring the TB epidemic under control. The aim of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
115
9
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(150 citation statements)
references
References 18 publications
21
115
9
5
Order By: Relevance
“…A qualitative approach at rural area of Tanzania did not found any patients being higher educated. 28 The result of present study was consistent with some other studies 5,7,29,30 as well. Economic barrier frequently causes obstruction for seeking health care facilities.…”
Section: Discussionsupporting
confidence: 83%
“…A qualitative approach at rural area of Tanzania did not found any patients being higher educated. 28 The result of present study was consistent with some other studies 5,7,29,30 as well. Economic barrier frequently causes obstruction for seeking health care facilities.…”
Section: Discussionsupporting
confidence: 83%
“…Despite almost 60% awareness, the proportion of respondents that knew that bacteria/germ is the cause of TB was very low (6.8%) which accords with earlier studies in Africa [26,[28][29][30][31], and Pakistan [32]. Among those who responded that they knew the cause of TB, 20.3% said it was due to smoking cigarette, 23.5% mentioned that it was caused by inhaling dust and 1.3% stated witchcraft, result at variance to what was reported from the study in eastern Nigeria (24).…”
Section: Don't Knowsupporting
confidence: 76%
“…Two studies conducted in two different settings at different time period documented similar findings of patient delay (60 days) [8] [15]. Whereas another two studies conducted in a population of similar setting reported significantly different patient delays (20 versus 60 days) [3] [8].…”
Section: Introductionsupporting
confidence: 56%
“…One study defined "patient delay" as the time interval between the onsets of TB symptoms-and the first formal or informal health care received [19]. Health system delay [6] [18], Medical provider delay [8] or Health service delay [15] was used to define the time interval from the first consultation at any formal health facility up to the date of diagnosis. Many other studies used the health system delay [3] [16] [20], health service delay [19] and health provider delay [7] more comprehensively to mean the time interval from first consultation up to treatment initiation.…”
Section: Introductionmentioning
confidence: 99%